ASK HEART GAME CARD DEVELOPMENT TO PROVIDE AN UNDERSTANDING OF MARRIAGE READINESS IN EARLY ADULTHOOD - Evinalisa, Yolinda; Afiati, Evi; Muhibah, Siti (Jurusan Bimbingan dan Konseling, 2024)
This research aims to provide an understanding of marriage readiness in early adulthood through the media of the Tanya Hati card game as an effort to fulfill one of the developmental tasks in early adulthood. Apart from that, this research was carried out as a form of optimizing the Guidance and Counseling program through the development of Guidance and Counseling media in the form of game cards. The research method used is “Research and Development” using the ADDIE model (analysis, design, development, implementation and evaluation). Data collection through observation, interviews and questionnaires. The research results show that the Tanya Hati card game media developed is very suitable for use with an average result of 85% from expert assessments. Based on limited trials on 8 students, the heart question card game media obtained a score of 84%. The research results show that the development of the Tanya Hati card game media is valid and effective as a medium that provides an understanding of marriage readiness in early adulthood.